Implementasi Moderasi Islam dalam Kegiatan Imtaq di MAN 2 Lombok Timur - Muhayan, Muhayan; Zaki, Muhammad; Maimun, Maimun (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Religious moderation has become a public discourse and has given birth to various meanings. This fact is one indicator of the importance of moderation, as seen in the development and variety of studies such as religious moderation, Islamic moderation, moderate Islam, and so on. This study aims to determine how the Madrasah Policy is in the implementation of Islamic moderation and the Implementation of Islamic moderation through Imtaq Activities at MAN 2 East Lombok. In this study, documentation, observation, and interviews are the methods used to collect data. The study results are the Madrasah Policy regarding the Implementation of Islamic Moderation Through Imtaq Activities at MAN 2 East Lombok. The efforts made by MAN2 East Lombok in implementing Islamic moderation through imtaq activities are as follows: 1) Information collection policy related to Islamic Moderation, 2) Integrative Policy of Islamic Moderation, and 3) Action policy towards instilling moderation values. Implementation of Religious Moderation in Learning at MAN 2 East Lombok The learning program has been integrated with the values ​​of religious moderation through teaching and learning activities (KBM), extracurricular activities (Imtaq), and habituation activities. In terms of content, these programs are related to the socio-cultural context, which not only teaches religion in the dzahiri aspect but also the spiritual aspect. However, in the implementation process, it is sometimes trapped in fanaticism and extremism which results in verbal violence and intolerance.